2017
DOI: 10.15421/011739
|View full text |Cite
|
Sign up to set email alerts
|

Use of soil biota in the assessment of the ecological potential of urban soils

Abstract: In assessing the ecological conditions and classification of urban soils, data about soil biota should be taken into account. The environment of urban territories is characterized by significant changes compared to their surrounding environments. It is established that the algal flora of urban soils lose their zonal features and features associated with the edification influence of higher plants. Specific biotopes with a definite species structure are formed in urboecosystems. Fifty 50 algae species have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
6
0
3
Order By: Relevance
“…Міське середовище впливає на формування флори -опосередковано (через зміну умов існування) і безпосередньо (за рахунок фізичного знищення рослин), перетворюючи її в строкатий конгломерат елементів як місцевого походження, так і сторонніх (Dyderski et al, 2017;Maltsev et al, 2017;Rejmánek, 2018). Урбанофлора -це сукупність видів, що самостійно існують на міській території.…”
Section: обговоренняunclassified
“…Міське середовище впливає на формування флори -опосередковано (через зміну умов існування) і безпосередньо (за рахунок фізичного знищення рослин), перетворюючи її в строкатий конгломерат елементів як місцевого походження, так і сторонніх (Dyderski et al, 2017;Maltsev et al, 2017;Rejmánek, 2018). Урбанофлора -це сукупність видів, що самостійно існують на міській території.…”
Section: обговоренняunclassified
“…Until now, the diversity of representatives of the genus Hantzschia among soil diatoms was reported as H. abundans Lange-Bertalot, H. amphioxys , H. elongata Grunow and H. vivax (W. Smith) Peragallo, including some of their varieties 26 – 34 . H. amphioxys , as the most commonly reported species, has been noted to occur in various ecosystems, from diverse soils, including alkaline 32 or calcareous 26 , soils of halophilic, shrub, meadow, and psammophytic phytocenoses 30 , soil horizons in artificial and natural forests of the steppe zone 33 , 35 , forest litter of pine, oak and white acacia plantations 36 , urban soils 37 and disturbed lands 38 . It was shown that H. amphioxys could dominate even in the steppe soil post-pyrogenic communities 39 and in biological soil crusts after the effects of fire 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The biomass of cultivated energy plants makes it possible to partially meet the needs for renewable energy resources, increases the intensity of carbon biosequestration. The use of the biomass for energy purposes is a priority for climate stabilization, contributes to plant biodiversity [Moroz 2018, Lemus 2002, Lopushnyak 2016b. A number of the cultivated plants are grown for energy purposes, including energy willow and poplar, miscanthus, switchgrass, sylphia, etc.…”
Section: Introductionmentioning
confidence: 99%